Kepercayaan Diri, Kematangan Emosi, Pola Asuh Orang Tua Demokratis dan Kenakalan Remaja - Fatchurahman, M. (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2012)
Abstract, The aims of this study is to investigate the correlations among the self-confidence, emotional maturity and the democratic-parenting with the youth delinquency. The subjects of this study were 46 students of class X of SMK Muhammadiyah,Malang. Based on the correlation and the regression analysis were obtained there were no correlation among the emotional maturity variable and the democratic parenting with the youth delinquency. Expectionally the self-confidence, there was significant and negative correlation with youth delinquency. The more self confidence, the less youth delinquency. Keywords: Self-confidence, emotional maturity, democratic parenting, youth delinquency.